Urinary Tract Infection with Atypical Mycobacteria - Thomas, Evan (J Urol, 1980)
We present a case of disseminated atypical mycobacterial (Mycobacterium intracellularis) infection of the urinary tract. The patient had anhydrous ectodermal dysplasia and an unrelated defect in cell-mediated immunity. The infection resulted in a lengthy ureteral stricture with resultant hydronephrosis and diminished kidney function. A review of the literature revealed only 13 previous cases of atypical mycobacterial infection of the urinary tract. It is important to distinguish between simple colonization by these organisms and actual infection. Differentiation between atypical mycobacterial infection and urinary tuberculosis is important in determining the therapeutic regimen.